Real-world effectiveness of biological therapy in patients with rheumatoid arthritis: Systematic review and meta-analysis - Castro, Caroline Tianeze de; Queiroz, Mariana Jorge de; Albuquerque, Flavia Caixeta; Brandão, Celmário Castro; Gerlack, Leticia Farias; Pereira, Daniella Cristina Rodrigues; Barros, Sandra Castro; Andrade, Wenderson Walla; Bastos, Ediane de Assis; Azevedo, Jessé de Nobrega Batista; Carreiro, Roberto; Barreto, Mauricio Lima; et al. (Frontiers in Pharmacology, 2022)
Background: The treatment of rheumatoid arthritis (RA), a chronic systemic inflammatory autoimmune disease, is based on disease-modifying anti-rheumatic drugs (DMARDs). Typically, it starts with conventional synthetic DMARDs (csDMARDs), and depending on the patient's response to the treatment and the adverse events experienced, biological DMARDs (bDMARDs) are initiated. bDMARDs are more specific to inflammatory factors than csDMARDs and more efficient in inducing remission and low disease activity. Thus, this study aimed to assess the effectiveness of biological therapy in patients with rheumatoid arthritis in administrative health databases. Methods: PubMed, Embase, Lilacs, Ovid, Scopus, and Web of Science databases were searched from inception to October 21, 2021, to identify observational studies that evaluated the effectiveness of biological therapy in patients with rheumatoid arthritis using administrative databases and real-world data. The methodological quality was assessed by the Methodological Index for Non-Randomized Studies (MINORS). A fixed or random-effects model estimated risk ratios with 95% confidence intervals. The analysis was divided into four groups: tumor necrosis factor inhibitors (TNFi) versus non-TNFi; TNFi versus TNFi (Adalimumab, Etanercept, and Golimumab versus Infliximab); bDMARDS versus Janus kinase inhibitors (JAKi); and bDMARDs monotherapy versus combination therapy (bDMARDs and MTX). Results: Twenty-one records were eligible for inclusion in this systematic review and meta-analysis; seven population-based cohorts, eight prospective, and six retrospective cohort studies. Overall, 182,098 rheumatoid arthritis patients were evaluated. In the meta-analysis, lower effectiveness was observed among TNFi users compared to non-TNFi (RR 0.88; 95% CI 0.81-0.95; p < 0.01; I2 = 94.0%) and bDMARDs compared to JAKi (RR 0.86; 95% CI 0.79-0.94; p < 0.01; I2 = 93.0%). Higher effectiveness among adalimumab, etanercept, and golimumab compared to infliximab (RR 1.19; 95% CI 1.05-1.36; p < 0.01; I2 = 96.0%) was found. No significant differences in the effectiveness of bDMARDs monotherapy compared to combination therapy (RR 0.83; 95% CI 0.68-1.00; p < 0.01; I2 = 81.0%) was observed. E‐value analysis indicated that the estimates were not robust against unmeasured confounding. Conclusions: According to the available real-world data, our results suggest that biological therapy effectively treats patients with rheumatoid arthritis, indicating higher effectiveness with non-TNFi and JAKi than TNFi.